AGREEMENTS BETWEEN PUBLIC PROSECUTOR AND DEFENDANT - Lečić, Boriša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The process of alignment of the Serbian legislation with the legal standards of the European Union has led to implementation of a number of legal institutes from the comparative law into the criminal procedure law of our country. One such institute is the agreement on consensual ways of terminating criminal proceedings. The agreements of the parties in the criminal procedure draw considerable attention and cause disputes among scientific and professional circles both in continental and Anglo-Saxon legal system, since the primary objective of law and justice should be unbiased and impartial determination of factual truth so that no innocent person would be convicted and the appropriate criminal sanctions would be imposed upon the perpetrator of a criminal offence. This paper analyses the agreements between a public prosecutor and a defendant, which emerged through the reform processes of the Serbian criminal proceedings. In this respect, the first part of this paper lays out the agreement on admission of committing a criminal act (formerly pleading guilty), the second presents the agreement on the testimony of the defendant, and the third - the agreement on the testimony of the convicted person. Although the agreements refer to the same subject, the distinction has to be made between the agreement on the admission of a criminal act, which includes the penal agreement and the indictment, and on the other hand the other two types of agreements on the testimony of the defendant and the convicted person. These are process institutes. In the case of agreement on the admission of a criminal offense, they speed up criminal proceedings and make them more efficient. In the case of agreement on testimony, they facilitate argumentation on the part of a public prosecutor for the most serious crimes that are by definition difficult to prove or their proving is associated with huge difficulties. The bargaining means used is improving the position of the defendant whose cooperation is rewarded with a more lenient criminal sanction.